2013
DOI: 10.1038/ijo.2013.202
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adipogenesis in 3T3-L1 cells and suppression of abdominal fat accumulation in high-fat diet-feeding C57BL/6J mice after downregulation of hyaluronic acid

Abstract: Changes in the ECM such as accumulation of high molecular weight of HA by HAS and degradation of HA by endogenous HYAL were essential for adipogenesis both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…Multiple applications of a hyaluronidase leading to a reduction in local HA content in C57BL/6J mice fed a high-fat diet resulted in significant (up to 35%) reduction of fat mass with simultaneous reduction of the size of the adipocytes [53]. These results were recently confirmed in [54], who also demonstrated inhibition of adipogenesis in 3T3-L1 cells after downregulation of HA levels in vitro . Whereas neither of these efforts focused on intradermal adipocytes, we can assume similarities to the modifications of dWAT observed in Col VI knockout mouse, since purified hyaluronidase is able to disrupt Col VI fibers as well [55].…”
Section: Is Dwat Metabolically Relevant?mentioning
confidence: 79%
“…Multiple applications of a hyaluronidase leading to a reduction in local HA content in C57BL/6J mice fed a high-fat diet resulted in significant (up to 35%) reduction of fat mass with simultaneous reduction of the size of the adipocytes [53]. These results were recently confirmed in [54], who also demonstrated inhibition of adipogenesis in 3T3-L1 cells after downregulation of HA levels in vitro . Whereas neither of these efforts focused on intradermal adipocytes, we can assume similarities to the modifications of dWAT observed in Col VI knockout mouse, since purified hyaluronidase is able to disrupt Col VI fibers as well [55].…”
Section: Is Dwat Metabolically Relevant?mentioning
confidence: 79%
“…Increased HA content has been demonstrated to facilitate monocyte adhesion and chemotaxis [24]. In contrast, the reduction of HA by exogenous hyaluronidase inhibits adipogenesis of 3T3-L1 cells [25]. Moreover, chronic treatment of HFD-fed obese mice with a PEGylated human recombinant hyaluronidase PH-20 decreases adiposity and adipose inflammation to prevent insulin resistance [26].…”
Section: Ecm Components In the Adipose Tissuementioning
confidence: 99%
“…In contrast, others have found that hyaluronan oligosaccharides increase MMP-13 expression which subsequently induces the loss of ECM proteoglycan and collagen in human articular cartilage [13,14]. Moreover, hyaluronan downregulation has been reported to have inhibitory effects on adipogenesis in 3T3-L1 cells in vitro and on fatty liver development in high-fat diet-fed C57BL/6J mice in vivo [15]. Furthermore, a direct inhibitory effect of hyaluronan fragment (HF) on adipogenesis has been demonstrated in 3T3-L1 preadipocytes [16].…”
Section: Introductionmentioning
confidence: 73%
“…Hyaluronan is a major component of ECM and is widely used in pharmaceutical and medical applications, such as arthritis treatment [18], ophthalmic surgery [19,20], drug delivery [21], and tissue engineering [22], owing to its unique physicochemical properties and various biological functions. It was reported that the downregulation of hyaluronan inhibited adipogenesis [15]. We previously reported a direct inhibitory effect of HF on adipogenesis or lipid droplet accumulation in 3T3 L1 preadipocyte [16].…”
Section: Discussionmentioning
confidence: 98%